The way of Chuang Tzu - Chuang-tzu; Merton, Thomas, 1915-1968. (London : Unwin Books, 1970)
Free renderings of selections from the works of Chuang-tzu, taken from various translations.
Bibliography: p. 158.
engund
1
Keywords: Philosophers, Chinese